HUBUNGAN FAKTOR KARAKTERISTIK INDIVIDU DAN KONDISI PEKERJAAN TERHADAP STRES KERJA PADA PERAWAT GIGI - Rian Rosihan Ansori; Tri Martiana (The Indonesian Journal of Public Health, 2017)
Job stress is an adaptive response and feedback adjustment in a condition individuals and the environment. Dental nurses face a variety of things in their duties that can cause stress, both physically and mentally. The objectives of this research are conducted to determine whether there is a correlation between individual characteristics and conditions of employment factors to the occurrence of occupational stress. The research was conducted with cross sectional design. By filling the questionnaire conducted to 22 dental nurses. Amount of samples used total population. The independent variables were the individual characteristics (age, sex, and years of marriage) and factor conditionsof employment (demand, support, ties up job roles). The result of the research showed that there was a strong relationship between job stress with sex, there was a strong relationship between job stress with the demands of work, there was enough relationship between job stress with age, tenure, support employment, labor relations and the role of work on dental nurses. The suggestion of results this study recommends that dental nurses need off work and do refreshing, providing training to dental nurses in improving the capability and skills. Relating to the implementation of the tasks, it’d better to conductjoint training among employees. They are aimed for the sake of increasing solidarity and friendshipness among colleagues. Giving rewards to employees are also recommended for the best achievement at work.Keywords: job stress, work period, work demands